Mathematics Discourse Communities: Language Ideologies and Urban Mathematics Teaching With Latinas/os. (March 2017) - Willey, Craig; Gatza, Andrew; Flessner, Courtney
This case explores how a monolingual teacher, embedded in a large urban school context, saw and understood her role in supporting emergent bilingual learners' development of mathematics discourse. Particular attention is paid to the classroom arrangements and curricular and instructional choices this teacher made to facilitate this development. The teacher maintains distinct language ideologies and perceptions of Latina/o learners that tacitly influence her design and implementation of mathematics discourse communities. Assuming that this phenomenon is widespread, this case raises questions about what educational leadership might do to shift the paradigm toward school culture where all school personnel understand the power of specialized discourses, the need to assume a collective responsibility to explicitly support learners' language development, and their inextricable connection to Latina/os' subject-area affinities and identities.